Pengembangan Aplikasi E-Booking Konser K-Pop Berbasis QRIS dengan Pendekatan User-Centered Design untuk Optimalisasi Pengalaman dan Efisiensi Transaksi - Ozmar Azhari; Putry Wahyu Setyaningsih; Septian Eka Ady Buananta; Fandevi Maitri; Francka Sakti Lee (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The increase in the number of K-Pop concerts in Indonesia drives the need for a ticket e-booking system that is not only efficient but also capable of accommodating transaction characteristics with high demand levels and optimal integration of digital payment systems. The main issue with the current e-ticketing system lies in the platform's general nature (multi-event marketplace) and the suboptimal integration of user experience with digital payment systems like QRIS. This research aims to design and develop a mobile-based K-Pop concert e-booking application integrated with QRIS and empirically test its impact on transaction efficiency and user experience. The method used is Research and Development (R&D) with a System Development Life Cycle (SDLC) Waterfall model approach, complemented by a quasi-experimental design (posttest control group design). Testing was conducted on 60 respondents divided into experimental and control groups, with variables measured including transaction time, transaction success rate, usability using the System Usability Scale (SUS), and user satisfaction. The research results show that the K-Party application is capable of effectively and integratively supporting the e-booking process. Statistical analysis shows that the use of QRIS has a significant impact on transaction efficiency and user experience, as well as contributing to business performance improvements, including a 36.2% increase in revenue and a 5-10% increase in audience numbers. Thus, the developed system is not only technically feasible but also empirically proven to add value in the context of the digital entertainment industry.